1982
DOI: 10.1148/radiology.142.1.6975953
|View full text |Cite
|
Sign up to set email alerts
|

Postembolic colonic infarction.

Abstract: From a total of 23 cases from five hospitals, acute colonic mucosal necrosis developed in three patients following transcatheter embolotherapy for colonic hemorrhage. Although embolic therapy for lower gastrointestinal bleeding is associated with appreciable risk, these risks are less than those of emergency operation for hemorrhage. The alternative transcatheter therapeutic modality, vasopressin infusion, is often associated with continued or recurrent hemorrhage, is relatively contraindicated in patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
41
1

Year Published

1992
1992
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(43 citation statements)
references
References 0 publications
1
41
1
Order By: Relevance
“…6 Given the lack of a dual blood supply in the lower GI tract, it was perceived that embolization could never effectively treat lower tract bleeding without compromising healthy enteric tissue. [7][8][9][10] However, innovations in coaxial technique have allowed for a superselective approach to bleeding vessels, resulting in continued high rates of haemostasis with reduced instances of ischaemia. Numerous studies in recent years have demonstrated this benefit, [11][12][13][14][15][16][17] contributing to the overall acceptance of embolization as a legitimate and even preferred treatment option in the management of acute massive colonic haemorrhage.…”
Section: Discussionmentioning
confidence: 99%
“…6 Given the lack of a dual blood supply in the lower GI tract, it was perceived that embolization could never effectively treat lower tract bleeding without compromising healthy enteric tissue. [7][8][9][10] However, innovations in coaxial technique have allowed for a superselective approach to bleeding vessels, resulting in continued high rates of haemostasis with reduced instances of ischaemia. Numerous studies in recent years have demonstrated this benefit, [11][12][13][14][15][16][17] contributing to the overall acceptance of embolization as a legitimate and even preferred treatment option in the management of acute massive colonic haemorrhage.…”
Section: Discussionmentioning
confidence: 99%
“…3 In early series, the incidence of colonic infarction was reported to be as high as 20%. The use of superselective embolisation to deliver particulate size of 100 µm or larger 4 into the most distal arterial branches has resulted in a reduction of this complication with only 10% requiring surgery for ischaemia.…”
Section: Discussionmentioning
confidence: 99%
“…Vasopressin infusion has been the treatment of choice in patients with mesenteric bleeding, often as a prelude to resection of the affected hemicolon. We have used vasopressin infrequently because hemorrhage is frequently not controlled or hemorrhage commonly recurs after discontinuation of vasopressin ( [8], KJ Cho, unpublished data). Furthermore, the vasoconstrictive effects of vasopressin may result in small bowel infarction and peripheral or myocardial ischemia [9,10].…”
Section: Discussionmentioning
confidence: 99%
“…The reported complications of mesenteric embolotherapy are mesenteric ischemia and colonic stricture [8,12,16,17]. The exact incidence of mesenteric ischemia following embolization is unknown because the complication will depend on the level, extent, and site of mesenteric arterial occlusion by embolization and the state of local collateral circulation.…”
Section: Discussionmentioning
confidence: 99%